2009
DOI: 10.1161/atvbaha.108.182428
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism

Abstract: Abstract-Patients who have a first episode of venous thromboembolism (VTE) have an elevated risk of a recurrent episode, and this necessitates secondary prophylaxis. Anticoagulant therapy is a double-edged sword, however, as it reduces the risk of recurrent VTE but increases the risk of hemorrhage. This balance must be taken into account when assessing the risk-benefit ratio of long-term anticoagulation. , is a common and preventable disease. The incidence of VTE in industrialized countries is around 1 to 2 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(48 citation statements)
references
References 119 publications
1
44
0
3
Order By: Relevance
“…Physicians may be more likely to prescribe LMWH monotherapy in NSCLC patients because of increased awareness of vascular events in these patients [25,26]. We found that patients with stage III cancer diagnosis and increasing age were less likely to receive LMWH.…”
Section: Discussionmentioning
confidence: 79%
“…Physicians may be more likely to prescribe LMWH monotherapy in NSCLC patients because of increased awareness of vascular events in these patients [25,26]. We found that patients with stage III cancer diagnosis and increasing age were less likely to receive LMWH.…”
Section: Discussionmentioning
confidence: 79%
“…The two major subtypes of VTE are deep vein thrombosis (DVT) and pulmonary embolism (PE). Patients who have had their first VTE episode have increased risk of recurrence,5, 6, 7, 8, 9 with the risk being highest in the first few months after the initial episode and remaining high through the first year 10. About a quarter of patients will have a recurrent episode within 5 years of their initial VTE episode and 30% are expected to have a recurrent episode within 10 years 10…”
Section: Introductionmentioning
confidence: 99%
“…However, since patients with unprovoked VTE are known to have a higher risk of recurrent VTE compared to those with provoked VTE (ie, VTE caused by transient risk factors such as surgery),5, 6, 8 the extent to which the finding in the overall VTE population could be applicable to the subset of patients with unprovoked VTE remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Fatal PE, the most serious consequence of VTE, ranges from 0.01% among low-risk surgical patients to 5% among hospitalised medical patients with multiple risk factors, and is currently considered the commonest avoidable cause of hospital death [4,5]. VTE is associated with a high risk of recurrence after a first event and, on cessation of anticoagulant therapy, approximately 10% of patients experience a recurrence within 1 year and up to 30% have a recurrence within 10 years [6,7]. In addition, VTE is associated with long-term clinically significant complications, which include the post-thrombotic syndrome and chronic pulmonary hypertension [4].…”
Section: Introductionmentioning
confidence: 99%